Combinatorial optimization of a molecular glass photoresist system for electron beam lithography - Bauer, Wolfgang-Andreas C (Advanced materials (Deerfield Beach, Fla.), 2011)
Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.